Proprioceptive Indicators of Personality and Individual Differences in Behavior in Children With ADHD - Liutsko, Liudmila; Iglesias, Tania; Tous Ral, Josep Maria; Veraksa, Alexander (Frontiers in Psychology, 2018)
Researchers have suggested that the link between personality traits and Attention-Deﬁcit/Hyperactivity Disorder (ADHD) could be a crucial factor in understanding the disorder’s diatheses. The aim of our study was to contribute to research on personality differences (based on fine motor precision – a novel approach) in children with and without ADHD symptoms. The Children Sustained Attention Task (CSAT) and Proprioceptive Diagnostics of Temperament and Character (DP-TC) were administered to children with an ADHD diagnosis and age-matched controls. Correlational and ANOVA analyses were performed to see the association between the results of both tests and the groups’ performance. Correlational analysis suggests significant relationships between some personality dimensions (DP-TC) and correct detection in a sustained attention task (CSAT). Statistically significant differences were found between the groups on the personality dimensions (DP-TC), with the following characteristics for ADHD children: (a) temperamental tendency to pessimism; (b) high temperamental excitability; (c) high Emotionality, and (d) Behavioral Rigidity (meaning also less adaptation to changes in the environment, in temperament and character). Correct detection in the sustained attention test was significantly correlated with reaction time and the personality variables Style of Attention and Irritability. The results also showed high proprioceptive Emotionality and lack of emotional control in children with ADHD. This is an exploratory study, investigating for the first time the differences in personality (based on fine motor precision) and the relation of personality traits to scores in sustained attention for children with and without ADHD.